IMPLEMENTASI PEMBELAJARAN PAI BERBASIS ADLX INTROFLEX DI SMAIT ISHLAHUL UMMAH PRABUMULIH - Nurgenti, Sheilda; Ardi Wahyudi (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to analyze the implementation of the Adlx Intriflex learning model in the Islamic Education (PAI) learning process at SMA IT Ishlahul Ummah Prabumulih. The Adlx Intriflex approach emphasizes active learning, deep understanding, and meaningful learning experiences for students. This study uses a qualitative descriptive method with data collection techniques including observation, interviews, and document analysis. Data validity is tested using triangulation techniques, namely data triangulation and source triangulation. Data analysis is carried out through three stages: data reduction, data presentation, and conclusion drawing. The results of the study show that the implementation of the Adlx Intriflex approach successfully increased students' active participation in the learning process. Learning is no longer passive but involves students directly through an experiential-based approach. Overall, the Adlx Intriflex approach can be an innovative alternative that is effective in improving the quality of PAI learning in schools.